2014
DOI: 10.3897/neobiota.20.5778
|View full text |Cite
|
Sign up to set email alerts
|

Forestry trial data can be used to evaluate climate-based species distribution models in predicting tree invasions

Abstract: Climate is frequently used to predict the outcome of species introductions based on the results from species distribution models (SDMs). However, despite the widespread use of SDMs for pre-and post-border risk assessments, data that can be used to validate predictions is often not available until after an invasion has occurred. Here we explore the potential for using historical forestry trials to assess the performance of climate-based SDMs. SDMs were parameterized based on the native range distribution of 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…During the field visits in the cities of Bloemfontein and Johannesburg, people that had A. cultriformis in their gardens reported that this species was present in many gardens in neighbouring areas. As this species has been widely planted, it is likely that the extensive seed bank and high climatic suitability (Motloung et al 2014) could make it a high invasion risk (Wilson et al 2011). Of the naturalised species that were detected in this study, A. cultriformis is the only one for which nation-wide eradication is likely to be not feasible (given the problems with locating all horticultural plantings).…”
Section: Discussionmentioning
confidence: 84%
“…During the field visits in the cities of Bloemfontein and Johannesburg, people that had A. cultriformis in their gardens reported that this species was present in many gardens in neighbouring areas. As this species has been widely planted, it is likely that the extensive seed bank and high climatic suitability (Motloung et al 2014) could make it a high invasion risk (Wilson et al 2011). Of the naturalised species that were detected in this study, A. cultriformis is the only one for which nation-wide eradication is likely to be not feasible (given the problems with locating all horticultural plantings).…”
Section: Discussionmentioning
confidence: 84%
“…For each species, we calculated the additional area of natural habitats that a species could potentially invade (based on 2009 land cover; source: South African National Biodiversity Institute). We subtracted the area known to be occupied (obtained from SAPIA, GBIF and forestry trials (Motloung et al ., )) from the area predicted to be suitable by the habitat suitability model (we only considered natural habitats). This represents the total area the species could occupy (based on 15‐min cells) without considering its density.…”
Section: Measuring Invasion Debt At Different Invasion Stagesmentioning
confidence: 99%
“…Alternative explanations are that foresters actively select areas where invasions are most likely to occur, i.e. by selecting environmental conditions very similar to those in the native ranges of the species (Donaldson et al 2014;Motloung et al 2014), or that invasions are simply driven by their introduction effort (propagule pressure), i.e. more plantings over a longer period provide more chances to spread.…”
Section: Global Biogeography and Invasion Ecology Of Wattlesmentioning
confidence: 97%